Kontribusi Disposisi Matematis terhadap Prestasi Belajar Matematika Siswa - Sinta Fanisia; Aniswita Aniswita (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research was motivated by the results of interviews and observations of researchers in class VII SMPN 1 Candung. The low mathematical disposition of students, this can be seen from the lack of self-confidence, interest and curiosity of students. Then the low achievement of students' mathematics learning, this can be seen from the scores of the odd semester midterms of students. There are still many students who get scores below the KKM, which is around 77.67%. The low mathematics learning achievement of students is suspected by several factors, including mathematical disposition. The objectives of this research are: a) to find out whether there is a relationship between mathematical dispositions and students' mathematics learning achievement in grade VII SMPN 1 Candung in the 2020/2021 academic year. b) to find out how big the contribution of mathematical disposition to students' mathematics learning achievement in grade VII SMPN 1 Candung in the 2020/2021 academic year. The data collection technique in this study used a mathematical disposition test and questionnaire. This study uses a significant correlation test. The results of the study obtained t_count = 4.434 and t_table = 1.703. So that t_count>t_table, then H0 is rejected and H1 is accepted, that is, there is a significant relationship between mathematical dispositions and mathematics learning achievement for class VII students of SMPN 1 Candung in the 2020/2021 academic year. This means that there is a contribution of mathematical disposition to the mathematics learning achievement of grade VII students of SMPN 1 Candung in the 2020/2021 academic year, which is 42.13%.Penelitian ini dilatarbelakangi oleh hasil wawancara dan observasi di kelas VII SMPN 1 Candung dan didapatkan informasi tentang rendahnya disposisi matematis siswa, hal ini dapat dilihat dari rasa percaya diri, minat dan rasa ingin tahu siswa yang kurang. Kemudian rendahnya prestasi belajar matematika siswa yang dapat dilihat dari nilai ujian tengah semester ganjil bahwa masih banyak siswa yang mendapatkan nilai dibawah KKM yaitu berkisar 77,67%. Rendahnya prestasi belajar matematika siswa diduga oleh beberapa faktor, salah satunya yaitu disposisi matematis. Oleh karena itu, tujuan dilaksanakannya penelitian ini adalah untuk mengetahui apakah terdapat hubungan antara disposisi matematis terhadap prestasi belajar matematika siswa di kelas VII SMPN 1 Candung Tahun Pelajaran 2020/2021 dan untuk mengetahui seberapa besar kontribusi disposisi matematis terhadap prestasi belajar matematika siswa di kelas VII SMPN 1 Candung Tahun Pelajaran 2020/2021. Teknik pengumpulan data dalam penelitian ini menggunakan tes dan angket disposisi matematis. Penelitian ini menggunakan uji kebermaknaan korelasi. Hasil penelitian diperoleh dan , sehingga , maka H0 ditolak dan H1 diterima yaitu terdapat hubungan signifikan antara disposisi matematis terhadap prestasi belajar matematika siswa kelas VII SMPN 1 Candung Tahun Pelajaran 2020/2021. Hal ini berarti terdapat kontribusi disposisi matematis terhadap prestasi belajar matematika siswa kelas VII SMPN 1 Candung Tahun Pelajaran 2020/2021 yaitu sebesar 42,13%.